Simulating fluid within elastic pipe(弹性管道约束下的流体仿真) - 杨少娟(YANG Shaojuan); 马龙(MA Long); 杨润泽(YANG Runze); 陈实(CHEN Shi); 周元峰(ZHOU Yuanfeng) (Zhejiang Daxue xuebao. Lixue ban)
Research on simulating the interaction of fluids in elastic pipes is a significant topic in the field of physical simulation. In this paper, we adopt position based dynamics to achieve high controllability and real-time performance. A hybrid approach is employed, using particles to simulate fluids, allowing for a more flexible representation of continuously flowing fluids while using triangular meshes to model pipes, enabling the establishment of overall elastic constraints. This approach comprehensively considers collisions within the pipe, ensuring the non-penetrative interaction between fluids and pipes, resulting in a realistic and closely coupled simulation. Additionally, elastic constraints are introduced to endow the pipe with specific elastic properties, and GPU parallel computing is utilized to accelerate the simulation. Experimental results indicate that the proposed approach is suitable for simulating particle-based fluids and triangular mesh-based pipes, providing an effective solution for simulating fluid flow within elastic pipes.(模拟流体和弹性管道之间的交互是物理仿真领域的重要研究方向。基于位置动力学方法进行了模拟，得到了高可控性和实时性结果。采用混合模型，其中，粒子模型用于流体建模，灵活模拟流动的流体；三角形网格模型用于管道建模，建立管道的弹性约束。全面考虑流体在管道内的碰撞情况，确保无穿透，实现流体与管道的紧密交互仿真。引入弹性管道约束，赋予管道一定的弹性特性，并利用GPU进行并行计算提升仿真速度。实验结果表明，所提算法适用于基于粒子的流体与基于三角形网格的管道的仿真，为弹性管道的流体仿真提供了有效的解决方案。)